2023
DOI: 10.5662/wjm.v13.i4.210
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of online systems to promote youth participation in research: A methodological study

Marie Salem,
Lance Pollack,
Alex Zepeda
et al.

Abstract: The documentation of psychological trauma is obviously a challenge to clinicians while they are diving deep into remote events related to their clients or patients. The potential role of psychological trauma in the early developmental stages, and even the existence of adverse childhood experiences, is important to prove, yet it is difficult to do so. A diverse range of methods have been applied, all of which presumably benchmark a big therapeutic step; however, these enthusiastic methods frequently do not last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous studies on the feasibility of different recruitment approaches have reported recruitment rates, that is, the ability to recruit a certain number of eligible individuals over a specified timeframe, as a way to evaluate the practicality and feasibility of different methods of outreach (Bowen et al, 2009;Brøgger-Mikkelsen et al, 2020;Orsmond & Cohn, 2015). To evaluate our recruitment approach, feasibility in the current study was defined as our team's ability to connect with 150 teens who met inclusion criteria for our digital intervention study using our two online recruitment methods over 6 months, a timeframe comparable to other digital intervention studies among teens (Ali et al, 2022;Salem et al, 2023;Smith et al, 2023). Both recruitment approaches were used for approximately 6 months in total.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on the feasibility of different recruitment approaches have reported recruitment rates, that is, the ability to recruit a certain number of eligible individuals over a specified timeframe, as a way to evaluate the practicality and feasibility of different methods of outreach (Bowen et al, 2009;Brøgger-Mikkelsen et al, 2020;Orsmond & Cohn, 2015). To evaluate our recruitment approach, feasibility in the current study was defined as our team's ability to connect with 150 teens who met inclusion criteria for our digital intervention study using our two online recruitment methods over 6 months, a timeframe comparable to other digital intervention studies among teens (Ali et al, 2022;Salem et al, 2023;Smith et al, 2023). Both recruitment approaches were used for approximately 6 months in total.…”
Section: Methodsmentioning
confidence: 99%